Pemberdayaan masyarakat Daerah Aliran Sungai (DAS) Kahayan di Kelurahan Palangka Kota Palangka Raya melalui program Ecoliteracy - Triyani Triyani; Syarpin Syarpin (Unri Conference Series: Community Engagement, 2022)
The waste problem is a serious problem faced by the people of the Kahayan Watershed (DAS), Palangka Village, Central Kalimantan. Pollution of the river due to the accumulation of garbage resulting from the daily activities of the community. The river, which in fact is the residence of the Palangka Village community, is polluted because of piles of garbage as a result of people throwing garbage into the river. This is exacerbated by the lack of public awareness to manage the environment in the watershed area, as well as the pattern of disposal of waste and garbage which water goes directly into the river. Based on these problems, it is necessary to have the right solution to overcome the waste problem that exists in the Kahayan Watershed (DAS) community, Palangka Village. Solutions to overcome these problems are 1) conducting counseling and training related to a healthy living culture to increase public knowledge and increase public awareness regarding the importance of a healthy living culture; 2) seeking the availability of landfills by paying attention to the separation of types of organic and inorganic waste and 3) conducting training related to waste processing. The results of the community service activities are the implementation of healthy living counseling activities, organic waste processing training, and the provision of landfills. The conclusion from the community service program that the team has implemented is that the Stimulus Community Partnership Service Program (PKMS) is going well and has received a positive response from the community.